Teachers’ perceptions and competencies in implementing individualized education program in inclusive primary schools - Tsalitsa Ifrocha; Slamet Subiyantoro; Eka Budhi Santosa (Universitas Sebelas Maret, 2026)
The implementation of inclusive education in elementary schools requires teachers to be prepared not only in terms of attitude, but also in terms of pedagogical competence in translating the individual needs of students into learning practices. This study aims to analyze teachers' perceptions and competencies in implementing Individualized Education Programs (IEPs) in inclusive elementary schools, as well as to examine the gap between perceptions and implementation practices in the classroom. The research used a qualitative approach with a case study design conducted at SD Negeri Nayu Barat 1 Surakarta. The research subjects consisted of three class teachers and the school principal, who were selected using purposive sampling. Data were collected through the SACIE-R questionnaire, learning observations, in-depth interviews, and IEP document analysis. The data were then analyzed using the Miles and Huberman interactive model. The results showed that teachers' perceptions of inclusive education were in the moderate to high category, but this was not in line with their IEP implementation competencies. A gap was found between perception and practice, influenced by mediating factors such as teachers' professional initiative, involvement in assessment, and structural factors such as the limited number of special assistant teachers and the high administrative burden on classroom teachers. These findings emphasize the importance of strengthening pedagogical competence and institutional support so that IEP implementation does not stop at administrative compliance but functions as a meaningful learning instrument.